Lipidomic Analyses Uncover Apoptotic and Inhibitory Effects of Pyrvinium Pamoate on Cholangiocarcinoma Cells via Mitochondrial Membrane Potential Dysfunction - Kittirat, Yingpinyapat; Phetcharaburanin, Jutarop; Promraksa, Bundit; Kulthawatsiri, Thanaporn; Wangwiwatsin, Arporn; Klanrit, Poramate; Sangkhamanon, Sakkarn; Jarearnrat, Apiwat; Thongchot, Suyanee; Mahalapbutr, Panupong; Loilome, Watcharin; Saya, Hideyuki; et al. (Frontiers in Public Health, 2021)
Pyrvinium pamoate (PP), an FDA-approved anthelmintic drug, has been validated as a highly potent anti-cancer agent and patented recently as a potential chemotherapeutic drug for various cancers. The aims of this study were, therefore, to investigate the ability of PP in anti-proliferative activity and focused on the lipid profiles revealing the alteration of specific lipid species in the liver fluke Opisthorchis viverrini (Ov)-associated cholangiocarcinoma (CCA) cells. PP inhibited CCA cell viability through suppressing mitochondrial membrane potential (MMP) and ATP productions, leading to apoptotic cell death. Liquid chromatography-mass spectrometry combined with chemometrics was performed to investigate lipid alteration during PP-induced apoptosis. The lipidomic analyses showed the altered lipid signatures of CCA cell types including S-acetyldihydrolipoamide, methylselenopyruvate and triglycerides that were increased in PP-treated CCA cells. In contrast, the levels of sphinganine and phosphatidylinositol were lower in the PP-treated group compared with its counterpart. The orthogonal partial-least squares regression analysis revealed that PP-induced MMP dysfunction, leading to remarkably reduced ATP level, was significantly associated with triglyceride (TG) accumulation observed in PP-treated CCA cells. Our findings indicate that PP could suppress the MMP function, which causes inhibition of CCA cell viability through lipid production, resulting in apoptotic induction in CCA cells. These findings provide insightful phenomena on an anti-cancer mechanism of PP under apoptotic induction ability that may serve as an alternative approach for CCA treatment.